Technical Analysis of Malaysia Stock Performance - FAM, CHING LEONG; Mohamad, Mahathir (Enhanced Knowledge in Sciences and Technology, 2022)
Technical analysis is a tool that investors used to determine the investment opportunities by examine the stock market using chart and technical indicators. However, there exist various type of technical tools can be used to examine the performance of stock market and traders might be unable to find indicate the best techniques and indicators for help them in determine the suitable stock to trade or invest. This study aim to predict the stock market price movement and also determine the ideal time to buy or sell the stock by using different technical approaches. The sample study consist of three largest capitalization company from Kuala Lumpur Stock Exchange (KLSE) which are TopGlove, AirAsia and Digi. The sample period taken from 1 June 2021 to 25 December 2021. The technical tools used in this study are Exponential Moving Average (EMA 9 days and 100 days), Simple Moving Average Cross (SMA 9 days and 26 days cross), candlestick chart pattern, Fibonacci Retracement, Moving Average Convergence Divergence (MACD), Relative Strength Index (RSI) and Stochastic Oscillators. The result of technical analysis show that technical tools can provided reliable trading information which are buy and sell signals and market trend of the sample study on the covered sample period to traders to make investment decisions.